Optimization Design and Dynamic Characteristics Analysis of Self-Responsive Anti-Falling Device for Inclined Shaft TBMs - Han Peng; Can Yang; Linjian Shangguan; Lianhui Jia; Bing Li; Chuang Xu; Wenjuan Yang (Machines, 2025)
To address the frequent failure of anti-falling devices in inclined shaft tunnel boring machines caused by cyclic loading and fatigue during construction, this study proposes an optimized self-responsive anti-falling device design. Based on the operational conditions of the “Tianyue” tunnel boring machine, a three-dimensional model was constructed using SolidWorks. Finite element static analysis was employed to validate structural integrity, revealing a maximum stress of 461.19 MPa with a safety factor of 1.71. Explicit dynamic simulations further demonstrated the dynamic penetration process of propellant-driven telescopic columns through concrete lining walls, achieving a penetration depth exceeding 500 mm. The results demonstrate that the device can respond to falling signals within 12 ms and activate mechanical locking. The Q690D steel structure exhibits a deformation of 5.543 mm with favorable stress distribution, meeting engineering safety requirements. The energy release characteristics of trinitrotoluene propellant and material compatibility were systematically verified. Compared to conventional hydraulic support systems, this design offers significant improvements in response speed, maintenance cost reduction, and environmental adaptability, providing an innovative solution for fall protection in complex geological environments.